GLOBAL STRATEGIES TOWARD 2030: ADVANCING EQUITABLE AND QUALITY ACCESS TO HIGHER, TECHNICAL, AND VOCATIONAL EDUCATION - Sa’diyah, Halimatus; Mohamed, Sheik (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
This article examines global strategies aimed at achieving equitable and quality access to higher, technical, and vocational education (HTVE) within the framework of the 2030 Sustainable Development Goals. Using a qualitative, literature-based approach, the study explores inclusive policies, innovative financing mechanisms, cross-sectoral collaborations, and the role of technology in expanding learning opportunities, particularly for marginalized groups. The findings reveal that a multidimensionalstrategy one that includes structural reform, industry engagement, and digital transformation is essential to address persistent disparities across diverse national contexts. The paper emphasizes that increasing access must be balanced with improvements in educational quality and relevance so that HTVE can meaningfully contribute to sustainable social and economic development. These insights offer valuable input for formulating more responsive and equity-driven global education policies.